2016
DOI: 10.1177/0957650916649329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of suction side blade profile on the performance of a side channel pump

Abstract: Due to the centrifugal effect of the radial impeller, side channel pumps are a kind of regenerative pumps that provide high head at low flow rate. The geometry of the impeller affects flow patterns and energy conversion directly, greatly influencing the performance of side channel pumps. To investigate the effect of blade profile for suction side on the performance of a side channel pump, three different base angles of 10 , 20 , and 30 , respectively, on the blade suction side were discussed and analyzed both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…Fleder and Böhle [23] presented a systematic and detailed examination on the effect of blade and side channel geometries on the hydraulic performance of a side channel pump. Recently, Zhang et al [24,25] revealed the effects of the blade suction angle on the head performance of the side channel pump. The main principle of operation of a side channel pump has been an intriguing phenomenon for many scholars over the years, with particular attention paid to the impeller.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fleder and Böhle [23] presented a systematic and detailed examination on the effect of blade and side channel geometries on the hydraulic performance of a side channel pump. Recently, Zhang et al [24,25] revealed the effects of the blade suction angle on the head performance of the side channel pump. The main principle of operation of a side channel pump has been an intriguing phenomenon for many scholars over the years, with particular attention paid to the impeller.…”
Section: Introductionmentioning
confidence: 99%
“…The pump is mainly made up of the inlet pipe, radial impeller blades, circular side channel and outlet pipe. The suction side of the impeller is profiled in an isosceles-triangular form with the suction angle of 30 • [24,25]. The inlet pipe is separated by the interrupter from outlet pipe to prevent reverse flow.…”
Section: Introductionmentioning
confidence: 99%
“…It was pointed out after the numerical simulations that the forward symmetric blade angles compared with the other models recorded higher coefficients of heads and displayed a better performance. Recently, Zhang together with his colleagues improved the head pressure performance of the side channel pump by varying the suction side blade angles from 0° to 30° as indicated in Figures and .…”
Section: Effects Of the Geometrical Design Of The Parameters Of The Smentioning
confidence: 99%
“…The impeller with various suction side blade profile angles indicating θ = 10°, θ = 20°, and θ = 30° [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Effects Of the Geometrical Design Of The Parameters Of The Smentioning
confidence: 99%
“…Fleder and Böhle [21] conducted numerical and experimental studies on different geometrical conditions such as blade length, blade width and side channel height to analyze the internal flow characteristics and its influence on the hydraulic performance of a side channel pump. Recently, Zhang et al [22,23] put forward that the greater blade suction angle, the higher the head performance. Even though, the blade suction angle had a minimal effect on the efficiency, the blades profiled with suction angle 30 • produced optimal performance compared to 10 • and 20 • .…”
Section: Introductionmentioning
confidence: 99%